2012
DOI: 10.4103/0971-4065.103912
|View full text |Cite
|
Sign up to set email alerts
|

Nondiabetic kidney disease in type 2 diabetic patients: A single center experience

Abstract: Nondiabetic renal disease (NDRD) is seen as a cause of proteinuria and renal failure in type 2 diabetes mellitus (DM). The clinical differences between NDRD and diabetic glomerulosclerosis (DGS) are not clear. This study was done to find the spectrum of NDRD in type 2 DM patients and differences in clinical profile between NDRD and DGS patients. Data of patients with type 2 DM who underwent renal biopsy in this institute from 1990 to 2008 were analyzed retrospectively. Patients were categorized as isolated NDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…Similarly to our results, the most common lesion in the US was focal and segmental glomerular sclerosis [31]. In other studies IgA nephropathy and minimal change disease were found to be the commonest NDRD [32,33]. It must be taken into consideration that the incidence and type of renal involvement depend on biopsy criteria and geographical distribution.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly to our results, the most common lesion in the US was focal and segmental glomerular sclerosis [31]. In other studies IgA nephropathy and minimal change disease were found to be the commonest NDRD [32,33]. It must be taken into consideration that the incidence and type of renal involvement depend on biopsy criteria and geographical distribution.…”
Section: Discussionsupporting
confidence: 88%
“…This study also shows that those with biopsy-proven NDRD have a better composite outcome of end stage renal disease and death. Our finding of high prevalence of NDRD in T2D is consistent with observations made by others (Chong et al, 2012;Das et al, 2012;Harada et al, 2013;Kleinknecht et al, 1992;Lee et al, 1999;Mazzucco et al, 2002;Olsen & Mogensen, 1996;Richards et al, 1992;Soni et al, 2006;Yaqub et al, 2012). These studies showed a variable prevalence of NDRD of 18-78%.…”
Section: Discussionsupporting
confidence: 95%
“…Estimated glomerular filtration rate (eGFR) declines prior to more severe macroalbuminuria in type 2 diabetes (T2D); hence a combination of eGFR and albuminuria can be used to stage and monitor patients (American Diabetes Association, 2013; Kidney Disease: Improving Global Outcomes (KDIGO) CKD Work Group, 2013). While diabetes is the major cause of renal disease in patients with diabetes, in about a third of patients, renal dysfunction is due to other causes (non-diabetic renal disease; NDRD) (Chong, Keng, Tan, et al, 2012;Das, Dakshinamurty, Prayaga, & Uppin, 2012;Harada, Akai, Sumida, et al, 2013;Kleinknecht, Bennis, & Altman, 1992;Lee, Chung, & Choi, 1999;Mazzucco, Bertani, Fortunato, et al, 2002;Olsen & Mogensen, 1996;Richards et al, 1992;Soni, Gowrishankar, Kishan, & Raman, 2006;Yaqub, Kashif, & Hussain, 2012). In the NDRD group, the treatment of renal disease may require a different strategy.…”
Section: Introductionmentioning
confidence: 96%
“…IgA nephropathy (15.6%) and membranous glomerulonephritis (13.3%). 23 The commonest NDRD were MCD (12.5%), tubuloin terstitial nephritis (10.4%) and LN (6.3%) in a study conducted by Das et al 24 LN was the second commonest SGD in the study (7.03%). As reported in other studies, LN is the only GD shown to have female predominance.…”
Section: Discussionmentioning
confidence: 99%